Factorial analysis on biovinegar production from pineapple waste using mixed strains - Yashini K., Selvanathan; Shalyda, Md Shaarani; N., Masngut (Universiti Malaysia Pahang, 2020)
One of the feasible approaches to oversee pineapple waste deposit without harming the environment is by converting these build-ups into value added items such as biovinegar. The objective of this work is to screen the fermentation parameter to identify the best condition and significant parameters affecting the fermentation. Five independent parameters were investigated, namely; temperature, fermentation time, addition of glucose, part and condition of waste. Fractional factorial design of Design Expert® software was used to investigate the effect of independent parameters as well as the interaction between parameters on the biovinegar production. The work was carried out by natural fermentation in which naturally occurred microorganism readily available on the raw materials (pineapple waste) was used. The result showed that the order of parameter significance in acid production was as follows: temperature > addition of glucose > fermentation time > part of waste > condition of waste. The interaction parameter of fermentation time and addition of glucose had the strongest effect on the acid production. The best fermentation condition was carried out using pineapple peel juice at 30 °C for 8 days in an anaerobic condition with 50 g/L glucose addition. Under these conditions, acid production was 1.12 % w/v in which acetic acid concentration was 0.94 % w/v. The product pH was recorded at 3.57. The product yield and productivity were recorded at 0.1699 g/g and 0.0489 g/L.h, respectively. Exploration on producing biovinegar using mixed strains and pineapple waste as substrate could be another way to reduce environmental pollution and at the same time turning this waste into value added product. Moreover, using the natural fermentation together with the carry over benefit of the pineapple benefitted the quality of produced biovinegar.